Self-reference and Legitimization in Popular Musics of Traditional Base from Cuyo (Revista Argentina de Musicología, 2016)
The purpose of this article is to gain depth in the analysis of popular musics of traditional base from Cuyo, focusing on some aspects of the themes that appear in the song’s literary texts. This is part of a bigger work that aims to unravel the mechanisms and factors of legitimization present among the cultivators of these musics and their implications in constructing the Cuyoan sociocultural identity.Peter Berger’s and Thomas Luckmann’s sociologies are the theoretical basis, especially for the way in which they worked with the concept of legitimization. The heterogeneous material contained in the corpus has been categorized following Gerard Genette’s theoretical and methodological approach. I incorporate some methodological procedures from Teun Van Dijk’s Critical Discourse Analysis, building axes through the productions and discourses relative to popular musics from Cuyo.With this framework and these tools, I intend to follow one analysis axis that I have called “self-reference”, studying the part of the corpus that refers to the lyrics of cuecas and tonadas.
Keywords: popular musics; legitimization; identities; self-reference